Psychosocial Aspects of Physical Difference: The Experiences of Eight Adults with Albinism in Puerto Rico. (November 2018) - Estrada-Hernandez, Noel
Introduction: This article explored the experiences of eight persons with albinism in Puerto Rico in their quest for educational, social, and employment opportunities. Methods: Volunteers participated in structured interviews that yielded the information presented in this article. Results: Four main areas were identified that best described the stories of these participants: knowledge of and attitudes toward albinism, resilience and other supports, the challenges of albinism, and current needs. Discussion: It is clear from the participants' stories that physical attributes are still a prime factor in determining a variety of interactions for persons with albinism, many with potential effects on quality of life. Implications for practitioners: This article contributes to the literature documenting psychosocial aspects of the albinism condition. It provides evidence that environmental barriers and attitudes generally affect interactions with persons with albinism, knowledge that can be used by professionals who work with individuals with albinism.